Hearing protectors - Calculations of the noise level at the protected ear - Behar, Alberto (Canadian Acoustics, 2004)
The risk of noise induced hearing loss, when wearing a hearing protector, can only be calculated with the knowledge of the noise level at the protected ear. Several methods are available for calculating this level, from the hearing protectors’ attenuation data. However, most available data are obtained from procedures not usually found in real world situations. Therefore, the results from the calculations are corrupt. This paper reviews some existing methods for the attenuation measurements and noise level calculations. Some ways to overcome the use of non-realistic attenuation data are suggested in the paper.